PENGARUH PESTISIDA TERHADAP KEHIDUPAN ORGANISME TANAH - Sodiq, Moch. (MAPETA, 2000)
The residues of applied pestisies in Agriculture were the major source of environmental contamination by pesticides. The choise of pesticide and its dose, the effect of the pesticide on target and non target organisms and circulation of residue in the evironment should be considered cerefully considered Organophosphorous. carbamate. and chlore hydrocarbon pestisides could decrease soil organism pupulation. Clorinated hydrocarbons were more peristence than orqanophosphorous and carbamate pesticides